Organised labour, labour market imperfections, and employer wage premia - Sabien Dobbelaere; Boris Hirsch; Steffen Müller; Georg Neuschäffer (Halle Institute for Economic Research (IWH), 2023)
This paper examines how collective bargaining through unions and workplace co-determination through works councils relate to labour market imperfections and how labour market imperfections relate to employer wage premia. Based on representative German plant data for the years 1999-2016, we document that 70% of employers pay wages below the marginal revenue product of labour and 30% pay wages above. We further find that the prevalence of wage mark-downs is signifi cantly smaller when organised labour is present and that the ratio of wages to the marginal revenue product of labour is significantly bigger. Finally, we document a close link between labour market imperfections and mean employer wage premia, that is wage differences between employers corrected for worker sorting.
Keywords: D22; J31; J42; J50; 330; collective wage agreements; employer monopsony; employer wage premia; labour market power; wage mark-downs; wage mark-ups; worker monopoly; works councils